The province of Laguna in the writing of Philippine national history - Gotiangco, Gil G., Jr. II (2003)
It is axiomatic that the writing of national histories is often a critical summation of developments that occurred in the local units. Integration is either sadly minimal or pleasantly extensive. In Philippine historiography due to various considerations, many provinces are scantily accounted for, while a select few are portrayed in more significant ways. The province of Laguna, interestingly, is one among the select few which had figured prominently in almost all cultural periods of Philippine history. Was this simply a historical quirk or is this historical feature borne out of numerous strategic geographical and political considerations? This paper is not intended to address comprehensively the linkage between local and national history. It is primarily designed to provide insights on the extent of Lagunas's portrayal in Philippine history. Probably many historical writers already know that Laguna had been depicted as early as. the prehistoric times. This remained to be a consistent feature of Philippine history in the succeeding centuries.